First genetic survey on the Montagu’s Harrier Circus pygargus breeding population in Italy (Avocetta, 2025)
Investigating genetic variability and differentiation in target populations of conservation concern is key, as poor genetic variability may further threaten their survival and persistence over time. Here we present the first genetic data for the Italian breeding population of the Montagu’s Harrier Circus pygargus, a declining migratory raptor species typical of steppe and agricultural landscapes, ranked as vulnerable at the national level. We analyzed four mitochondrial genes, the cytochrome oxidase gene (COXI), control region (D-loop), 16S RNA subunit gene (16S), and NADH dehydrogenase 2 gene (ND2), in six individuals from central Italy to estimate their phylogenetic relationships with European populations and assess local genetic variation. We recorded low genetic nucleotide diversity (π = 0.0009), but relatively high haplotype diversity (h = 0.8) compared to Central European populations and a close phylogenetic relationship of Italian Montagu’s Harriers with both western and eastern European populations. This study can serve as a baseline to study genetic variability and conservation of this vulnerable raptor species in Italy.
Keywords: Accipitridae; breeding population; Circus pygargus; migration; mitochondrial DNA